Edukasi swamedikasi obat herbal yang rasional pada kelompok ibu rumah tangga di Kelurahan Karya Baru - Rosdah, Ayeshah Augusta; Adenina, Masayu Syarinta; Parisa, Nita; Harahap, Debby Handayati; Lusiana, Evi; Fatmawati, Fatmawati (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Indonesian Health Survey reported that more than half of the population in South Sumatera utilizes herbal medicine to alleviate disease symptoms. The survey also indicated that factors such as lower-middle income levels and the female gender are relatively more likely to utilize medicinal plants compared to higher-income levels and the male gender. The findings from this health survey strongly support the characteristics of the target audience for this community service, specifically the residents of Karya Baru Village represented by the women in Majelis Taklim Al-Kahfi. Initial interviews with several members of this group revealed a tendency to self-treat sick family members, particularly using herbal remedies, as they are perceived to have no side effects compared to modern medications (synthetic drugs). These findings indicate a potential irrational use of herbal medicine in self-medication practices. Self-medication refers to the efforts made by individuals to determine treatments for their disease symptoms. For self-medication practices to be safe and effective, it is essential for the community to be equipped with adequate knowledge about the rational use of herbal medicines. Therefore, a community service initiative is necessary to enhance public knowledge regarding the types of herbal medicines and promote rational behaviors on self-medication practice of herbal medicines within the community.